Technical Condition Assessment and Modelling of Reed Valves in Vehicle Engine Intake Systems - Oleksandr Kravchenko; Alexander Khrulev; Juraj Gerlici; Oleksii Saraiev; Serhii Danets (Communications)
The purpose of the study was to evaluate the effectiveness of using a simple reed valve model of an engine with periodic workflow. To achieve this purpose, models of the reed valve have been developed and determined that the quasi-stationary model allows one to find the air flow through the reed valve with an accuracy of 5-6%. The limits of permissible values, at which the model has a minimal error, correspond to Strouhal number of 0.2-0.3. This data confirmed that with proper consideration of the existing limitations, the quasi-stationary model gives results close to those provided by the complex dynamic models.